The COT2 gene is required for glucose-dependent divalent cation transport in Saccharomyces cerevisiae. - Conklin, D S (1993)
Eleven cobalt-tolerant mutants were found to belong to a single complementation group, cot2. In addition to cobalt, the cot2 mutants were found to tolerate increased levels of the divalent cations Zn2+, Mn2+, and Ni2+ as well. All of the cot2 mutants exhibited a wiener-shaped cellular morphology that was exacerbated by the carbon and nitrogen source but was unaffected by metals. The rate of glucose-dependent transport of cobalt into cells was reduced in strains that carry mutations in the COT2 gene. COT2 is not essential for growth. Strains that carry a COT2 allele conferring complete loss of function are viable and exhibit phenotypes similar to those of spontaneous cot2 mutations. The sequence of the COT2 gene shows that it is identical to GRR1, which encodes a protein required for glucose repression. The glucose dependence of the transport defect implies that cot2 mutations affect the link between glucose metabolism and divalent cation active transport.